Aspects of Islamic Tolerance with the Covenanted (Dhimmi): Doctrinal Jurisprudence Study - Al Salaymeh رنا مازن (Dirasat: Shari’a and Law Sciences, 2022)
Objectives: Explanation of the concept of tolerance, which is one of the most important Islamic concepts approved by Sharia for freedom of belief and acceptance of the other. The study also aims to clarify the doctrinal controls and the legal rulings that Islam sets in dealing with the people of Dhimma, and to highlight the social image between Muslims and the people of Dhimmis. Methods: The research relied on three approaches, namely: the inductive, analytical, and descriptive approach, in which the scientific material was traced from the approved sources and references, analyzed and clarified, this was based on the Qur’anic evidence, the Prophet’s Sunnah, the opinions of the famous jurisprudential schools, and the definition of the term tolerance. Results: The position of Islam in dealing with Dhimmis is based on tolerance and justice, They have the right to perform their religious rituals, and Muslims have the right to congratulate them on their occasions, and to greet them, and Islam has not prevented muslims from conducting various transactions with them in accordance with the doctrinal controls and legal provisions. Conclusions: Commitment to the tolerance of Islam with the people of Dhimma, respect for freedom of belief, and acceptance of the other within the doctrinal and legal controls.